Kata Ganti Nama dan Representasi Identiti Pewacana Parlimen: Pronouns and Identity Representations of Parliamentary Speakers (KEMANUSIAAN The Asian Journal of Humanities, 2023)
In a discourse of political interaction, the use of pronouns can indirectly reflect the identity of the speakers involved, specifically the government’s or opposition’s member of parliament. Besides being used to refer to a person, personal pronouns (PP) can describe the form of social relationship built between the speakers and the audience. This study aims to identify the form of the first personal pronoun utilised by government and opposition discourse as well as explain the identity highlighted through the use of PP based on critical discourse analysis approach. The text of the 2019 Budget debate is used as study data. A preliminary review of this study found that in both government and opposition discourse, the use of singular first PP “saya” is dominant compared to the use of plural first PP. For the plural PP, the use of “kita” inclusively is dominant in the opposition, while the the use of “kita” exclusively is dominant in the government. Similarly, both discourses are seen trying to “stand out” on their own, stand up, have a personal touch, and even try to get closer to their target audience. In comparison, the opposition emphasises the nature of belonging and togetherness with its discourse audience, while the government emphasises the nature of party which is seen as trying to strengthen the party’s position as the “new ruler” in the new Malaysian parliament.Dalam wacana interaksi politik, penggunaan kata ganti nama dalam ujaran secara tidak langsung dapat mencerminkan identiti pewacana yang terlibat, khususnya ahli parlimen kerajaan dan pembangkang. Selain berfungsi sebagai perujukan, pemanfaatan kata ganti nama diri (KGND) dapat menggambarkan bentuk hubungan sosial antara pewacana dan khalayaknya. Kajian ini bertujuan mengenal pasti bentuk KGND pertama yang dimanfaatkan oleh pewacana kerajaan dan pembangkang serta menjelaskan identiti yang diserlahkan menerusi penggunaan KGND berpaksikan pendekatan analisis wacana kritis. Teks perbahasan Belanjawan 2019 dijadikan data kajian. Tinjauan awal mendapati kedua-dua pewacana mendominasi penggunaan KGND pertama tunggal “saya” berbanding KGND pertama jamak. Bagi KGND jamak, pembangkang mendominasi “kita” inklusif, sebaliknya kerajaan mendominasi “kita” eksklusif. Secara persamaan, kedua-dua pewacana dilihat cuba “menonjolkan diri” secara sendirian, berpendirian, mempunyai sentuhan peribadi, dan juga cuba merapatkan diri dengan khalayak sasarannya. Secara perbandingan, pembangkang menyerlahkan sifat kekitaan dan kebersamaan dengan khalayak wacananya, manakala kerajaan lebih menyerlahkan sifat kepartian yang cuba mengukuhkan kedudukan parti selaku “pemerintah baharu” di Parlimen Malaysia Baharu.